Manipulation of Multielectron Dynamics of Molecules by Fourier-Synthesized Intense Laser Pulses: Effective Potential Analysis of CO - Ohmura, Shu; Ohmura, Hideki; Kato, Tsuyoshi; Kono, Hirohiko (Frontiers in Physics, 2021)
We present a theoretical investigation as to how multielectron dynamics of CO are manipulated by Fourier-synthesized intense laser pulses. The pulses used are assumed to be comprised of harmonics up to the fourth order. The multiconfiguration time-dependent (TD) Hartree-Fock (MCTDHF) method, where the multielectron wavefunction Ψ(t) is expressed as a linear combination of various electron configurations, is employed to simulate the dynamics of CO interacting with Fourier-synthesized pulses. The multielectron nature such as electron correlation is quantified by using our effective potential approach. To begin with, the time-dependent natural orbitals {ϕj(r,t)} which diagonalize the first order reduced density matrix are obtained from Ψ(t), where r is the one-electron coordinate. The effective potentials υjeff(r,t) that determine the dynamics of ϕj(r,t) are then derived from the equations of motion for {ϕj(r,t)}. υjeff(r,t) consists of the one-body part υ1(t) including the interaction with the laser electric field ε(t) and the two-body part υ2,j(t) originating from electron-electron interaction. In this way, the role of electron correlation can be quantified by comparing υjeff(r,t) with those obtained by the TDHF method, where Ψ(t) is approximated by a single Slater determinant. We found a very similar profile in υ5σeff(r,t) of the 5σ highest occupied molecular orbital for both near-infrared one-color (ω) and directionally asymmetric ω+2ω two-color pulses; when ε(t) points from the nucleus C to O, a hump appears in υ5σeff(r,t) only 2 bohrs outward from C. The hump formation, which originates from the field-induced change in υ2,5σ(t) (especially, due to electron correlation), is responsible for preferential electron ejection from the C atom side (experimentally observed anisotropic ionization). A coherent superposition of ω and 2ω fields with an appropriate relative phase thus works as a one-color pulse of which either positive or negative peaks are filtered out. More sophisticated manipulation is possible by adding higher harmonics to a synthesized field. We show that the 5σ orbital can be squeezed toward the inside of the potential valley in υ5σeff(r,t), which encloses the molecule at a radius of ∼7 bohrs (semicircle in the region of z <0), by adjusting the phases of a ω+2ω+3ω+4ω field. The hump and valley formation in υ5σeff(r,t) are closely correlated with domains of increasing and decreasing electron density, respectively.